Cultural-linguistic explorations into spirituality, emotionality, and society - Wolf, Hans-Georg, 1963-; Latic, Denisa; Finzel, Anna (Cognitive linguistic studies in cultural contexts,, 2021)
"This book offers Cultural-Linguistic explorations into the diverse Lebenswelten of a wide range of cultural contexts, such as South Africa, Hungary, India, Nigeria, China, Romania, Iran, and Poland. The linguistic expedition sets out to explore three thematic segments that were, thus far, under-researched from a cultural linguistic perspective - spirituality, emotionality, and society. The analytical tools provided by Cultural Linguistics, such as cultural conceptualizations and cultural metaphors, are not only applied to various corpora and types of texts but also recalibrated and renegotiated. As a result, the studies in this collective volume showcase a rich body of work that contributes to the manifestation of Cultural Linguistics as an indispensable paradigm in modern language studies. Being a testament to the inseparability of language and culture, this book will enlighten academics, professionals and students working in the fields of Cultural Linguistics, sociology, gender studies, religious studies, and cultural studies"--